Potential Criminalization of Beating a Nusyuz Wife in Islamic Law: an Examination of Law No. 23 of 2004 Concerning The Elimination of Domestic Violence - Junaidi, M; Absori, Absori; Rizka, Rizka; Hakim, Rusydi; Budiono, Arief (Faculty of Law, Universitas Pekalongan, 2024)
In the case of so much the role of the husband towards his wife, the Shari'a gives legitimacy to husbands to beat nusyuz wives. However, the permissibility of hitting a wife to educate is not explained clearly in the Qur'an, how to beat her or when it is permissible, so that this beating has the potential to be punished according to Law No. 23 Years of Articles 5 and 6 concerning the elimination of Domestic Violence (KDRT). The gap that occurs between the prohibition of domestic violence as regulated in the law and the permissibility of hitting one's wife in Islamic law becomes an ongoing polemic if there is no bright spot for an in-depth discussion that has the potential to criminalize Islamic law. This research uses a normative doctrinal approach. The main data source is secondary data in the form of documents. This research is descriptive in nature which explains in detail the data collection and the current situation. The data collection technique is done by means of literature. The data analysis method of this paper is normatively qualitative, initially identifying through various forms of documents. Next, examine the data obtained from the field and literature by studying the rule of law to generate data and conclusions from the materials obtained by the researcher. From this research, it was found that the hitting procedure that has been put forward by the opinion of the Syafi'i, Hanafi, and Hanbali schools is categorized as a misdemeanor in Article 44 paragraph (4) of the 2004 PKDRT Law, because this procedure of hitting basically causes pain, inflicted by the husband on his wife, and this physical violence does not cause illness or hinder the victim's ability to work, carry out his position, or carry out daily activities. Meanwhile, Imam Malik's opinion requires that the procedure for hitting him should not be painful or cause pain, so that he does not qualify as a crime of physical violence in the PKDRT Law.